Astronomical Surveys and Active Galaxies - Mickaelian, A. M.; Abrahamyan, H. V.; Paronyan, G. M.; Mikayelyan, G. A.; Andreasyan, R. R.; Sukiasyan A. G.; Hambardzumyan, L. A.; Mkrtchyan, V. K.; Gasparyan, A. A.
Astronomical Surveys are the main source for discoveries in astronomy. We are giving the most important parameters the significance of the surveys, their main products: images, photometric, spectroscopic and other data. Among the surveys, namely extragalactic ones, most important are those for Active Galaxies (both Active Galactic Nuclei (AGN) and Starburst (SB) Galaxies), and particularly the AGN. These objects reveal many spatial and physical characteristics helping understanding the Universe. We give a brief review of our searches and studies for Active Galaxies.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture